Poor correlation between intracranial pressure and intraocular pressure by hand-held tonometry - Golan S (Dove Medical Press, 2013)
Shani Golan,1 Shimon Kurtz,1 Daphna Mezad-Koursh,1 Michael Waisbourd,1 Anat Kesler,1 Pinchas Halpern2 1Departments of Ophthalmology, Tel Aviv Sourasky Medical Center, affiliated with the Sackler Faculty of Medicine, Tel Aviv University, Tel Aviv, Israel; 2Emergency Medicine, Tel Aviv Sourasky Medical Center, affiliated with the Sackler Faculty of Medicine, Tel Aviv University, Tel Aviv, Israel Purpose: The aim of this study is to provide data on the controversial issue of whether handheld measurements of intraocular pressure (IOP) are capable of accurately predicting elevated intracranial pressure (ICP) in patients undergoing lumbar puncture (LP). Methods: All patients over the age of 18 years who underwent an LP in the emergency or neurological departments at the Tel Aviv Medical center for any reason between October 2007 and July 2010 were eligible to participate in this prospective observational pilot study. IOP was measured with the Tono-Pen XL while patients were in the supine position before undergoing LP. ICP was measured in the lateral recumbent position. ICP and bilateral IOP were measured, and the mean and maximum values of IOP were calculated. The association between ICP and each one of the four IOP measures was evaluated by the Pearson correlation coefficient. Results: Twenty-four patients (mean age 37.8 ± 15.8 years, ten males and 14 females) were enrolled. The reasons for their requiring an LP were headache (19/24 patients), evaluation for hemiparesis (2/24), cognitive deterioration (1/24), and seizures (2/24). Nine had elevated mean opening pressure (>20 cm H2O), six had an elevated mean IOP (>20 mmHg), and four of these six also had an elevated opening pressure. There was no significant correlation between the ICP measurements and any of the IOP measurements. Conclusion: Handheld ocular tonometry has poor sensitivity and specificity for the prediction of increased ICP and is not an effective tool for screening for ICP in the ED or in the neurology department. Keywords: ocular tonometry, Tono-Pen, IOP, intraocular pressure, ICP, intracranial pressure